Kaposi's sarcoma infiltrating skeletal muscle. Issue 6 (1st December 2002) - Haddow, L J; Davies, S; Buckingham, S; Miller, R F
Abstract : An HIV-1 antibody positive black African man with plasma cell variant Castleman's disease and cutaneous Kaposi's sarcoma, despite receiving chemotherapy, had progressive disease. In addition, he developed pain and swelling behind the right knee. Histology of an ultrasound guided biopsy showed Kaposi's sarcoma infiltrating the head of gastrocnemius.